Correlation between the outcomes and severity of diabetic ketoacidosis: A retrospective pilot study - George, John Titus (J Family Med Prim Care, 2018)
INTRODUCTION: Diabetic ketoacidosis (DKA) is a serious acute metabolic complication of diabetes mellitus (DM). It is classified into mild, moderate, and severe based on severity as per the American Diabetes Association (ADA) guidelines. There are limited data on the correlation between the severity of DKA and its outcomes using this classification system. The aim is to study the correlation between the outcomes and severity of DKA in a tertiary care center in India. METHODOLOGY: In this retrospective pilot study, 1527 patients with DM were identified over a span of 3 years, of which 63 had a discharge diagnosis of DKA and 37 fulfilled the ADA criteria for DKA. Following inclusion details on clinical parameters and outcomes of patients with mild, moderate, and severe DKA were compared. RESULTS: Mild, moderate, and severe DKA accounted for 8%, 41%, and 51% of the patients, respectively. Intensive Care Unit (ICU) care was required in 6.7% and 47.4% of those with moderate and severe DKA, respectively. Invasive ventilation (IV) was required in 47% (9) of those with severe DKA only. The mortality rates were 13.3% and 26% among those with moderate and severe DKA. The mean expenditure was ₹29,000, ₹30,000, and ₹64,000 among those with mild, moderate, and severe DKA, respectively. CONCLUSIONS: The ADA classification of severity of DKA correlates well with the duration of inhospital stay, costs of care, requirement of ICU care, need for IV or non-IV, and mortality. This suggests that this classification system could be a valuable tool in predicting outcomes.